The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.18203/2349-3291.ijcp20212757
|View full text |Cite
|
Sign up to set email alerts
|

Clinical profile and outcome of children with congenital heart diseases admitted with acute events in a paediatric tertiary care unit in North Karnataka

Abstract: Background: Congenital heart diseases are the predominant causes of paediatric morbidity and mortality. This study was done to know the clinical profile, various acute presentations, and risk factors for repeated hospitalizations and their outcome in children with congenital heart diseases.Methods: This prospective observational study of children in the age group of 0 hour-12 years, who were previously diagnosed and or newly diagnosed with congenital heart diseases.Results: A total of 102 children were present… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 7 publications
0
1
0
Order By: Relevance
“…13 In Egypt frequency of cousin marriages is 37% and incidence of congenital anomalies is 11.4%. 14 According to a recent study conducted in Pakistan prevalence of congenital anomalies was 40% in families with history of cousin marriage as compared to 26% in non-related parents. 15 In our study congenital anomalies were found in 31(1.6%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…13 In Egypt frequency of cousin marriages is 37% and incidence of congenital anomalies is 11.4%. 14 According to a recent study conducted in Pakistan prevalence of congenital anomalies was 40% in families with history of cousin marriage as compared to 26% in non-related parents. 15 In our study congenital anomalies were found in 31(1.6%) cases.…”
Section: Discussionmentioning
confidence: 99%
“…Congenital heart disease is the most prevalent congenital anomaly in the pediatric age group with prevalence of 0.6% to 9% and contributes to higher rate of morbidity and mortality [1,2]. Congenital heart disease is defined as the heart or intra-thoracic great vessel structural abnormalities present since birth with significantly functional irrespective of their detection age [3,4].…”
Section: Introductionmentioning
confidence: 99%